Analisis Yuridis Terhadap Tindak Pidana Perampasan Kendaraan Bermotor Oleh Debt Collector Dalam Praktek Leasing di Indonesia (Studi Putusan No. 176/Pid.B/2018/PN. Lbo) - Hesty Tanjung Wigianti; Widi Nugrahaningsih; Hery Dwi Utomo; Evi Elisanti (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study aims to determine 1) the legal analysis of the criminal act of unilateral confiscation of motor vehicles by debt collectors in leasing practices in Indonesia (Study of Decision No. 176/Pid.B/2018/PN. Lbo). 2) the legal responsibility of leasing companies for the criminal act of unilateral confiscation of motor vehicles carried out by debt collectors in leasing practices in Indonesia (Study of Decision No. 176/Pid.B/2018/PN. Lbo). This research method uses a normative legal approach. The type of data used is secondary data. Secondary data is data obtained through literature studies. The secondary data of this study are primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique is carried out through literature studies. The data analysis technique used is qualitative analysis. Qualitative data analysis because it is integrated with the activities of data collection, data reduction, data presentation, and conclusions from research results. The results of the study indicate that the study shows that the decision Number 176 / Pid.B / 2018 / PN Lbo, the taking of motor vehicles by debt collectors without the consent of the debtor, without a legal execution procedure, and accompanied by elements of coercion or threats, fulfills the elements of a criminal act as regulated in Article 365 of the Criminal Code (theft with violence) or Article 368 of the Criminal Code (extortion), depending on the modus operandi and legal facts in the trial. This confirms that the action is not just a matter of civil default, but has entered the criminal realm. Leasing companies can be held legally responsible as an extension of the financing company based on the principle of vicarious liability, the provisions of Article 1367 of the Civil Code for unlawful acts committed by debt collectors as long as they carry out their duties. Decision No. 176 / Pid.B / 2018 / PN Lbo shows that the pretext of using a third party does not eliminate the company's legal responsibility. If a debt collector commits an unlawful act in the process of billing or repossessing a vehicle, the leasing company can be held accountable either criminally, civilly or administratively and is liable under consumer protection law.